2015
DOI: 10.1007/s00425-015-2267-7
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing reveals differential expression of miRNAs in tomato inoculated with Phytophthora infestans

Abstract: The characterization and compare expression profiling of the miRNA transcriptome lay a solid foundation for unraveling the complex miRNA-mediated regulatory network in tomato resistance mechanisms against LB. MicroRNAs (miRNAs) are a class of small endogenous non-coding RNAs with 20-24 nt. They have been identified in many plants with their diverse regulatory roles in biotic stresses. The knowledge, that miRNAs regulate late blight (LB), caused by Phytophthora infestans, is rather limited. In this study, we us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 50 publications
6
44
0
Order By: Relevance
“…Computational analysis has identified 78 mRNAs as potential target transcripts of 14 milRNAs from M. anisopliae 39 A number of miRNAs-like RNAs have been identified in the plant fungal pathogen Sclerotinia sclerotiorum by high-throughput sequencing11. In our previous study, some miRNAs in P. infestans, including miR1918, were predicted from the P. infestans EST data and all the known miRNAs from miRBase27. P. infestans and tomato are two unrelated organisms, but both contain the conserved sequence of miR1918, and therefore studying the function of miR1918 would be of great significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational analysis has identified 78 mRNAs as potential target transcripts of 14 milRNAs from M. anisopliae 39 A number of miRNAs-like RNAs have been identified in the plant fungal pathogen Sclerotinia sclerotiorum by high-throughput sequencing11. In our previous study, some miRNAs in P. infestans, including miR1918, were predicted from the P. infestans EST data and all the known miRNAs from miRBase27. P. infestans and tomato are two unrelated organisms, but both contain the conserved sequence of miR1918, and therefore studying the function of miR1918 would be of great significance.…”
Section: Discussionmentioning
confidence: 99%
“…Late blight is caused by the pathogen Phytophthora infestans . Our previous work have focused on the use of high-throughput sequencing to identify tomato miRNAs related to resistance against P. infestans as well as on the functional analysis of P. infestans -induced miRNAs in tomato, including miR169, miR398, miR482, miR6024 miR6026, miR6027272829. MiR1918 is expressed in all tomato tissues, and it was initially thought to be involved in the regulation of fruit development and maturation30.…”
mentioning
confidence: 99%
“…Most of the R genes are represented by the gene family, which encodes proteins containing both nucleotide binding site (NBS) and leucine-rich repeat (LRR) (Dangl and Jones 2001). Recently, it has been observed that miR482, miR6024, miR6026 and miR6027 were down-regulated in P. infestans-and PSTVd-infected tomato leaves (Luan et al 2015;Sun et al 2014;Tsushima et al 2015). Although they are variable in sequence and abundance in different species, these miRNAs were identified to target transcripts of predicted functional R genes in tomato (Li et al 2012a).…”
Section: Mirnas and Host Defensementioning
confidence: 99%
“…et al (2010),Feng et al (2013b),Jin and Wu (2015),Lang et al et al (2010),Feng et al (2011),Jin and Wu (2015),Luan et al (2015),Naqvi et al et al (2012), (2013a), Jin et al (2012), Naqvi et al (2010), Tsushima et al (2015) miR162 B. cinerea, CMV, PSTVd, TAV, ToLCV DCL1 Cillo et al (2009), Diermann et al (2010), Feng et al (2011), Jin and Wu (2015), Naqvi et al et al (2009), Feng et al (2009), Jin and Wu (2015), Luan et al (2015), Naqvi et al et al (2009), Feng et al (2013b), Jin and Wu (2015), Lang et al (2011), Tsushima et al al. (2010), Feng et al (2012), Lang et al (2011), Naqvi et al et al (2009), Feng et al (2013a), Jin and Wu (2015), Lang et al (2011), Naqvi et al et al (2013b), Jin et al (2012), Naqvi et al (2010), Sun et al (2014) miR171 B. cinerea, CMV, PSTVd, TAV, ToLCV SCL Feng et al (2013a), Jin et al (2012), Lang et al (2011), Naqvi et al (2008), Tsushima et al et al (2010), Feng et al (2013a), Jin and Wu (2015), Naqvi et al et al (2009), Diermann et al (2010), Feng et al (2013b), Jin and Wu (2015), Lang et al et al (2010), Jin and Wu (2015), Lang et al (2011), Luan et al (2015), Naqvi et al PSTVd, P. syringae NBS-LRR Jin and Wu (2015), Luan et al (2015), Shivaprasad et al (2012), Sun et al -LRR Luan et al (2015), Sun et al (2014), Tsushima et al (2015) SPL squamosa promoter-binding protein-like, MYB myeloblastosis, ARF auxin response factor, DCL dicer-like, HD-ZIP homeodomain leucine zipper, NAC NAM/ATAF/CUC, AGO argonaute, NF-YA nuclear transcription factor Y subunit alpha, SCL scarecrow-like, AP2 apetala 2, TCP TEOSINTE BRANCHED/CYCLOIDEA/PCF GRF growth regulating factor, CSD copper/zinc binding superoxide dismutase, UBE ubiquitin conjugating enzyme, NBS-LRR nucleotide binding site-leucine-…”
mentioning
confidence: 96%
“…Among these miRNAs, miR171, miR408, and miR398 were found to be upregulated at a high level after R. solani treated 6, 12, and 24 h (Luo et al, 2015). Besides, Luan et al (2015) found a total 70 miRNAs which were manifested to change significantly in samples treated with P. infestans using high-throughput sequencing, including 50 downregulated miRNAs and 20 upregulated miRNAs. Moreover, miRNAs that may be involved in plant disease can be further studied combined with the analysis of target genes.…”
Section: Introductionmentioning
confidence: 99%